2003
DOI: 10.1103/physrevlett.91.014101
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in Oscillator Networks: Are Smaller Worlds Easier to Synchronize?

Abstract: Small-world and scale-free networks are known to be more easily synchronized than regular lattices, which is usually attributed to the smaller network distance between oscillators. Surprisingly, we find that networks with a homogeneous distribution of connectivity are more synchronizable than heterogeneous ones, even though the average network distance is larger. We present numerical computations and analytical estimates on synchronizability of the network in terms of its heterogeneity parameters. Our results … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
593
2
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 790 publications
(620 citation statements)
references
References 42 publications
(59 reference statements)
21
593
2
4
Order By: Relevance
“…Many recent papers have investigated various facets of this relation. For example, some papers have reported correlations between network synchronizability and degree homogeneity [9][10][11], clustering coefficient [12], degree correlations [13], average degree, degree distribution, and so on [14]. In some cases the observed correlations can point in opposite directions; for instance, [9] finds that increasing the degree homogeneity improves synchronizability, whereas [14] and [13] report cases of better synchronizability for decreased homogeneity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many recent papers have investigated various facets of this relation. For example, some papers have reported correlations between network synchronizability and degree homogeneity [9][10][11], clustering coefficient [12], degree correlations [13], average degree, degree distribution, and so on [14]. In some cases the observed correlations can point in opposite directions; for instance, [9] finds that increasing the degree homogeneity improves synchronizability, whereas [14] and [13] report cases of better synchronizability for decreased homogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…For example, some papers have reported correlations between network synchronizability and degree homogeneity [9][10][11], clustering coefficient [12], degree correlations [13], average degree, degree distribution, and so on [14]. In some cases the observed correlations can point in opposite directions; for instance, [9] finds that increasing the degree homogeneity improves synchronizability, whereas [14] and [13] report cases of better synchronizability for decreased homogeneity. Similarly, adding a few shortcut links to a sparse lattice is known to decrease the characteristic path length and improve synchronizability at the same time [15,16], although another study showed that better synchronization can result despite increased average distance [9].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, due to the realization that many networks in nature have complex topologies, these studies have been extended to systems where the pattern of connections is local but not necessarily regular [23,24,25,26,27,28,29,30,31,32]. Usually, due to the complexity of the analysis some further assumptions have been introduced.…”
Section: Synchronization: Kuramoto's Modelmentioning
confidence: 99%
“…The spectral information of the Laplacian matrix has been used to understand the structure of complex networks [41], and in particular to detect the community structure [42,43] (also the spectral analysis of the modularity matrix [44] can be used to this end). Recent studies have also focused on the spectral information of the Laplacian matrix and the synchronization dynamics [23,24,25,26,27,28,29,30]. The common approach is to take advantage of the master stability equation [45] to determine the relation between the relative stability of the synchronized state (via the ratio λ N /λ 2 ) and the heterogeneity of the topology, although sometimes some language abuse appears and authors talk about better or worse synchonizability instead of stability of the synchronized state.…”
Section: The Connection Between Synchronization and Topologymentioning
confidence: 99%
“…Since the average path length becomes short in small-world networks, synchronization is achieved more easily than in a regular lattice [10][11][12][13]. However, this is not the only condition; synchronizability also depends on the network size, the degree distribution (distribution of the number of links), the clustering coefficient, and so forth [14][15][16][17]. These studies are mainly based on the idea that the connections between cells promote in-phase synchronization.…”
Section: Introductionmentioning
confidence: 99%